An application of the SERVQUAL model to study the quality perceived by customers in a pizzeria - dos Santos, Lucas Oliveira; Muniz, Emerson Cleister Lima; Pereira, Emily Nadine; Dandolini, Gertrudes Aparecida; de Souza, João Artur (Revista Gestão da Produção Operações e Sistemas, 2021)
Purpose - To propose a set of measures to improve the services provided by a company in the food sector by adapting and applying the SERVQUAL model. Design/methodology/approach – This study uses a survey to collect data and information about the object being analyzed by giving questionnaires to the company's customers. For this, the population was defined along with the ideal sample to be achieved using the Simple Random Sampling method, considering a 5% sampling error and 95% reliability. Findings - The findings indicate a negative general evaluation in all five dimensions of quality analyzed, highlighting that only 17.4% of the 23 items analyzed in the study had positive results in the relational analysis between expectation and perception compared to the 82.6% that do not present this. Originality/Value - The in-depth analysis carried out in this study gave entrepreneurs a more detailed view of the actual state of the establishment, indicating the points that need to be improved urgently and that have directly affected the negative evaluation obtained by the establishment. The need to set up a better marketing plan, a change to the location of the establishment, and the urgent improvement of safety, were highlighted as items identified that need immediate change. Keywords: Food services. Quality in services. SERVQUAL. Satisfaction analysis. Pizzerias.